NZ J Ecol 2016
DOI: 10.20417/nzjecol.40.24
|View full text |Cite
|
Sign up to set email alerts
|

The legacy of Big South Cape: rat irruption to rat eradication

Abstract: Big South Cape Island (Taukihepa) is a 1040 ha island, 1.5 km from the southwest coast of Stewart Island/Rakiura, New Zealand. This island was rat-free until the incursion of ship rats (Rattus rattus) in, or shortly before, 1963, suspected to have been accidentally introduced via local fishing boats that moored at the island with ropes to the shore, and were used to transport the mutton birders to the island. This incursion was reported by the muttonbirders -local Iwi who harvest the young of titi (sooty shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Losses of biodiversity have been most severe on islands, where endemic species are often predatornaïve (Courchamp et al 2003). The invasion and subsequent irruption of ship rats on Big South Cape Island/ Taukihepa in 1963 led to the extinction of two endemic birds, a bat species, a large weevil and the local extinction of an additional four bird species (Bell 1978;Ramsay 1978;Bell et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Losses of biodiversity have been most severe on islands, where endemic species are often predatornaïve (Courchamp et al 2003). The invasion and subsequent irruption of ship rats on Big South Cape Island/ Taukihepa in 1963 led to the extinction of two endemic birds, a bat species, a large weevil and the local extinction of an additional four bird species (Bell 1978;Ramsay 1978;Bell et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The island is visited seasonally by small groups of people collecting mutton birds and was rat-free until the 1960s (Bell 1978). By 1964 however, ship rats (R. rattus) were well established throughout the island, and damage to the mutton-birders' cabins, bedding and stored food supplies was evident (Bell et al 2016). There was subsequently a marked decline in birdlife, invertebrates, and some plants including both local and global extinctions (Bell 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Prevailing knowledge at the time of the invasion also suggested that the introduction must have been a human-assisted dispersal. Fishing boats working in the area, possibly even those that transported the mutton-birders, were generally suspected as the source of the rats (Bell et al 2016), although where the rats might have boarded such boats was an open question. Once again in hindsight, at only 1.5 kilometres offshore, Big South Cape Island is within the known swimming range of Norway rats (Russell & Clout 2005), and while it is outside the known swimming range of ship rats (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations